(untitled) (AYUSHDHARA, 2025)
The unique concept of Anupana is well explained in Ayurveda as an adjuvant to therapeutic drug, which can be given either before or after or along with drug or diet and has the properties that can counteract the disease and can facilitate the drug action. There are specific Anupanas mentioned for different Sneha dravyas. As the special Anupana for Taila is Yusha, and general Anupana is Ushna jala, this study intends to observe the therapeutic effect of Ushnajala and Mudga yusha as Anupana for Shodhananga snehapana in hyperlipidemia which is a burning issue with a prevalence 25-30% of urban and 15-20% in rural subjects and has close resemblance with “Abaddha Medas”, Dhamani Praticchaya”, “Dhamani Upalepa” etc. The study was a comparative clinical study with pre and post-test design involving 2 groups with 20 subjects in each group. In Group A Ushnajala was given as Anupana for Shodhananga tailapana and in group B Mudga yusha was given followed by Virechana in both the groups. The assessment of Sneha Jeeryamana lakshanas, Sneha jeerna lakshanas, Samyak snigdha lakshanas and pre and post lipid profile were done. In group B the Sneha jeeryamana lakshanas were seen for a shorter duration, Sneha Jeerna lakshanas were observed quickly compared to group A with p value <0.001 for most of the subjective parameters. There was highly significant reduction in lipid values in both the groups with p value <0.001 in both the groups. Based on the result it can be concluded that Mudga yusha anupana for Shodhananga tailapaana is better than Ushna Jala anupana.